THE INFLUENCE OF SPIRITUAL LEADERSHIP ON EMPLOYEE PERFORMANCE IN SHARIA BANKS: QUALITY OF WORK LIFE (QWL) AND JOB SATISFACTION AS A MEDIATOR - Saefudin, Saefudin; Novitaningtyas, Ivo; Muh Nurul Huda; Suko Rina Adibatunabillah (JURNAL MANAJEMEN DAKWAH, 2024)
The performance of sharia banking in Indonesia has decreased during the Covid-19 pandemic. Moreover, the Covid-19 pandemic situation can increase mental and emotional pressure on employees at the office, as well as in Sharia banking. Therefore, it is necessary to increase leadership that is based on principles Islamic ethics in the context of Sharia banking to improve employee performance. This research aims to analyze banking performance Sharia in Indonesia through the development of spiritual leadership based on principles Islam, and also to examine the mediating role of quality of work life (QWL) and employee satisfaction. Research that examines the influence of spiritual leadership on employee performance, especially using the four pillars of Islamic principles, such as: Truthfulness (Al-Sidq); Trust (Trust); Communication (Tabligh); Knowledge (Fathonah) is still limited in the Shariah Bank context. A quantitative approach with a survey design was used to collect data from 1.131 Shariah Bank employees. The data analysis technique used structural equation modeling with partial least squares (SEM-PLS). Spiritual leadership has a significant effect on the quality of work life (QWL), job satisfaction and employee performance. In addition, QWL and job satisfaction mediate the effect of spiritual leadership on employee performance. Sharia banking can implement spiritual leadership to improve employee performance, especially in Indonesia after the Covid-19 pandemic. This research fills the literature gap by explaining the relationship between spiritual leadership, creativity, quality of work life, job satisfaction, and employee performance in the context of Shariah Banking in Indonesia.